Pengembangan Bahan Ajar Fisika Berbasis SETS (Science, Environment, Technology, and Society) Untuk Meningkatkan Kreativitas Peserta Didik - Zulfaniar; Muhammad Arsyad; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2024)
This research is Research and Development (R&D). The development is carried out by referring to the 4D model. The 4D stages include the define, design, develop and disseminate stages. This development research aims to: produce SETS (science, environment, technology, and society-based physics teaching materials to improve students' creativity that meet valid criteria; produce SETS-based physics teaching materials to improve students' creativity that meet practical criteria; describe the effectiveness of using SETS-based physics teaching materials to improve students' creativity that has been developed. The instruments used in this study were SETS-based teaching material validation sheets, practitioner assessment questionnaires, namely physics subject teachers, and creativity test instruments. The criteria for the practicality of the physics teaching module are seen from the assessment of practitioners (physics teachers), and the criteria for increasing creativity after the application of SETS-based physics teaching materials are seen from the increase in students' creativity test results. Based on the analysis results, it was obtained that: SETS-based physics teaching materials developed based on expert assessment using the Aiken V index analysis were declared valid and feasible to use; SETS-based physics teaching materials reviewed from practitioner assessments were in the very practical category; the effectiveness of increasing student creativity after using SETS-based physics teaching materials analyzed with N-gain of 72% was in the effective criteria.